Physical activity limitation as measured by accelerometry in pulmonary arterial hypertension. - Pugh, Meredith E; Buchowski, Maciej S; Robbins, Ivan M; Newman, John H; Hemnes, Anna R (CHEST, 2012)
Background: The 6-min walk test, commonly used to assess exercise capacity and response to therapy in pulmonary arterial hypertension (PAH), has many well-described limitations. Sedentary time is associated with adverse cardiovascular outcomes and reduced quality of life, and measuring sedentary time and physical activity using accelerometry is another potential way to quantify exercise capacity in PAH. Whether sedentary time is different in patients with PAH vs control subjects is unknown.Methods: Physical activity was measured in 20 patients with PAH and 30 matched healthy control subjects using accelerometry for 7 consecutive days. Patients with PAH completed standard 6-min walk testing, and baseline demographics were recorded for all study participants. Total daily activity counts, sedentary time, and proportion of time at various activity levels were compared between groups.Results: Sedentary time was significantly higher in patients with PAH (mean, 92.1% daily activity; 95% CI, 89.5-94.8%) than in control subjects (mean, 79.9% daily activity; 95% CI, 76.4%-83.5%; P < .001), and all levels of physical activity were reduced in the PAH group compared with the control group ( P < .01 for all). Daily moderate to vigorous physical activity was reduced in the PAH group (7.5 min; 95% CI; 0.8-15.6 min) compared with the control group (mean, 64.7 min; 95% CI, 51.1-78.2 min; P < .001). Activity counts correlated with 6-min walk distance in the PAH group (Spearman rank correlation 5 0.72, P < .001).Conclusions: Sedentary time is increased in patients with PAH and may lead to increased risk for metabolic and cardiovascular morbidity. Quantitation of daily activity and sedentary time using accelerometry may be a novel end point for PAH management and clinical trials.